Overexpression of STX11 alleviates pulmonary fibrosis by inhibiting fibroblast activation via the PI3K/AKT/mTOR pathway - Guichuan Huang; Xiangsheng Yang; Qingyang Yu; Qun Luo; Chunrong Ju; Bangyan Zhang; Yijing Chen; Zihan Liang; Shu Xia; Xiaohua Wang; Dong Xiang; Nanshan Zhong; et al. (Signal Transduction and Targeted Therapy)
Abstract Fibroblast activation plays an important role in the occurrence and development of idiopathic pulmonary fibrosis (IPF), which is a progressive, incurable, and fibrotic lung disease. However, the underlying mechanism of fibroblast activation in IPF remains elusive. Here, we showed that the expression levels of STX11 and SNAP25 were downregulated in the lung tissues from patients with IPF and mice with bleomycin (BLM)-induced lung fibrosis as well as in the activated fibroblasts. Upregulation of STX11 or SNAP25 suppressed TGF-β1-induced activation of human lung fibroblasts (HLFs) via promoting autophagy. However, they failed to suppress fibroblast actviation when autophagy was blocked with the use of chloroquine (CQ). In addition, STX11 or SNAP25 could inhibit TGF-β1-induced fibroblast proliferation and migration. In vivo, overexpression of STX11 exerted its protective role in the mice with BLM-induced lung fibrosis. STX11 and SNAP25 mutually promoted expression of each other. Co-IP assay indicated that STX11 has an interaction with SNAP25. Mechanistically, STX11-SNAP25 interaction activated fibroblast autophagy and further inhibited fibroblast activation via blocking the PI3K/AKT/mTOR pathway. Overall, the results suggested that STX11-SNAP25 interaction significantly inhibited lung fibrosis by promoting fibroblast autophagy and suppressing fibroblast activation via blocking the PI3K/ATK/mTOR signaling pathway. Therefore, STX11 serves as a promising therapeutic target in IPF.